(untitled) (Physical Education, Health and Social Sciences, 2025)
Social media has changed the way businesses connect with consumers, influencing how people shop through ads, influencer marketing, and online engagement. Platforms like Facebook, Instagram, and YouTube allow brands to promote their products directly to target audiences. This paper explores how social media usage, advertising, and influencer marketing affect consumer buying behavior, with a focus on how income levels play a role in these interactions. Consumer behavior is influenced by many factors, including emotions, social trends, and financial status. Social media marketing has become one of the most effective ways to reach consumers, as influencers and targeted ads shape purchasing decisions. Influencer marketing, in particular, has gained popularity because people trust recommendations from influencers more than traditional advertisements. Additionally, social media ads use advanced data targeting to reach the right audience based on their interests and behaviors. However, income level affects how consumers respond to these marketing strategies. People with higher incomes are more likely to buy luxury products and brand-name items, while those with lower incomes focus more on affordability, discounts, and promotions. This study examines how income influences consumer reactions to social media marketing, suggesting that while social media increases engagement and purchase intent, the level of impact depends on a person’s financial situation. By reviewing existing research, this paper highlights how businesses can adjust their digital marketing strategies to appeal to different income groups. The findings suggest that companies should tailor their campaigns based on consumers’ spending power to maximize marketing effectiveness. Future research should explore additional factors like cultural differences and psychological influences on consumer behavior. Understanding these trends will help businesses create more effective marketing strategies and build stronger relationships with their audiences in the digital world.